The role of platelet CD154 in the modulation in adaptive immunity - Sprague, Daniel L.; Sowa, Jennifer M.; Elzey, Bennett D.; Ratliff, Timothy L. (Immunologic research, 2007)
Platelets' primary role is hemostasis. However, a growing body of research has demonstrated that platelets are integral to the initiation of an inflammatory response and are potent effector cells of the innate immune response. Activated platelets express CD154, a molecule critical to adaptive immune responses, which has been implicated in platelet-mediated modulation of innate immune responses and inflammation. Recent studies utilizing CD154 knockout mice extend the role of platelet-derived CD154 to the modulation of adaptive immune response by enhancing antigen presentation, improving CD8+ T cell responses, and playing a critical function in T-dependent humoral immunity under physiological conditions. Together these data provide a basis for the expansion of the current paradigm of B cell activation and germinal center formation to include a role for platelets.